Iso-α-Acids, Bitter Components in Beer, Suppress Inflammatory Responses and Attenuate Neural Hyperactivation in the Hippocampus - Ano, Yasuhisa; Yoshikawa, Misato; Takaichi, Yuta; Michikawa, Makoto; Uchida, Kazuyuki; Nakayama, Hiroyuki; Takashima, Akihiko (Frontiers in Pharmacology, 2019)
Due to the growth in aging populations worldwide, prevention and therapy for age-related cognitive decline and dementia are in great demand. We previously demonstrated that long-term intake of iso-α-acids, which are hop-derived bitter compounds found in beer, prevent Alzheimer’s pathology in a rodent model. On the other hand, the effects of iso-α-acids on neural activity in Alzheimer’s disease model mice have not been investigated. Here, we demonstrated that short-term intake of iso-α-acids suppresses inflammation in the hippocampus and improves memory impairment even after disease onset. Importantly, we demonstrated that short-term administration of iso-α-acids attenuated the neural hyperactivation in hippocampus. In 6-month-old 5×FAD mice exhibiting hippocampus inflammation and memory impairment, oral administration of iso-α-acids for 7 days reduced inflammatory cytokines, including MIP-1α and soluble Aβ and improved object memory in the novel object recognition test. In 12-month-old J20 mice, intake of iso-α-acids for 7 days also suppressed inflammatory cytokines and soluble Aβ in the brain. Manganese-enhanced magnetic resonance imaging (MEMRI) of hippocampi of J20 mice showed increased manganese compared with wild type mice, but iso-α-acids canceled this increased MEMRI signal in J20 mice, particularly in the hippocampus CA1 and CA3 region. Taken together, these findings suggest that short-term intake of iso-α-acids can suppress hippocampus inflammation even after disease onset and improve hyper neural activity in Alzheimer’s disease model mice.